Prenatal prediction of osteogenesis imperfecta (OI type IV): exclusion of inheritance using a collagen gene probe. Issue 7 (July 1987) - Tsipouras, P; Schwartz, R C; Goldberg, J D; Berkowitz, R L; Ramirez, F
Abstract : Autosomal dominant osteogenesis imperfecta is caused by mutations in the COL1A2 and COL1A1 genes of type I collagen. In a family with OI type IV genetically linked to the COL1A2 gene, we attempted prenatal diagnosis in a pregnancy at risk by genotyping the DNA of the fetus for a COL1A2 gene associated RFLP. Our results showed that the fetus inherited the normal COL1A2 allele from her affected parent. Linkage analysis can thus be used in the prenatal diagnosis of dominantly inherited osteogenesis imperfecta.